Heat insulation of objects of higher risk - Sazonova Yu. (Zenodo, 2016)
About a fifth of the territory of Russia is located in the Arctic, there resides about 1.5 million people and is located about 30 large and medium cities. Another significant factor is the concentration of the territories north of the 67th parallel and mastered a large number of promising deposits of minerals: oil and gas among them. In connection c mining and processing of natural resources necessary to develop construction technologies in extremely low natural temperatures and permafrost. Construction in these areas has become one of the priorities of modern technological development, which provides for the establishment of special construction systems, focused on the construction of high-risk facilities in the Arctic. These objects include marine tankers, oil and gas platforms, equipment for the transport of oil, gas reducing installation and installation of oil refining. In each of the above objects, you must choose the right insulation, which will provide a high insulation capacity, and be fire-resistant and durable.